Combining Ability Studies in Elite Breeding Lines of Brinjal (Solanum melongena L.) for Plant Characters - Mishra, Ramanand; Singh, Anand K.; Vani, V. Manju; Singh, B. K.; Kumar, Harit; Rajkumar, B.V. (Asian Journal of Biological and Life Sciences, 2013)
Combining ability effects were estimated for seven different characters in brinjal comprising of thirty six hybrids obtained by crossing twelve lines and three testers by line × tester matting design. Significant differences were observed among the parents and hybrids/crosses for gca and sca effects respectively. Analysis of gca effects for parents revealed that the lines, Punjab Neelam, DBSR¬31, Ramnagar Giant, BR-SPS-14, ABSR-2 and Pant Rituraj were identified as most promising parents for inclusion in hybridization programme with the aim to improving fruit yield as well as other important yield and yield contributing characters. Crosses exhibiting high per se performance and significantly positive Sca effects for fruit yield and some other important characters were Punjab Sanyog x Black Beauty, Arka Nidhi x Dudhiya, DBSR-31 x Pant Rituraj, Ramnagar Giant x Dudhiya, BR-SPS-14 x Pant Rituraj, Pusa Uttam x Dudhiya, ABSR-2 x Dudhiya and ABSR-2 x Black Beauty. These crosses may exploit in the breeding programme for obtaining transgressive segregants towards developing hybrid varieties.